2018
DOI: 10.1111/gcb.14137
|View full text |Cite
|
Sign up to set email alerts
|

Nongrowing season methane emissions–a significant component of annual emissions across northern ecosystems

Abstract: Wetlands are the single largest natural source of atmospheric methane (CH ), a greenhouse gas, and occur extensively in the northern hemisphere. Large discrepancies remain between "bottom-up" and "top-down" estimates of northern CH emissions. To explore whether these discrepancies are due to poor representation of nongrowing season CH emissions, we synthesized nongrowing season and annual CH flux measurements from temperate, boreal, and tundra wetlands and uplands. Median nongrowing season wetland emissions ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
151
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(195 citation statements)
references
References 71 publications
(171 reference statements)
20
151
2
Order By: Relevance
“…In this study, the cold season fluxes resulted in differences in modeled NEE among land cover types (Figure a) but contributed little to the interannual variability of modeled NEE (Figure b). Modeled nongrowing season CH 4 flux measurements were also important for variability among land cover types in this study (Figure c), but not as important for interannual variability (Figure d), similar to recent findings across many sites (Treat, Bloom, & Marushchak, ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the cold season fluxes resulted in differences in modeled NEE among land cover types (Figure a) but contributed little to the interannual variability of modeled NEE (Figure b). Modeled nongrowing season CH 4 flux measurements were also important for variability among land cover types in this study (Figure c), but not as important for interannual variability (Figure d), similar to recent findings across many sites (Treat, Bloom, & Marushchak, ).…”
Section: Discussionsupporting
confidence: 89%
“…Fluxes of CH 4 persisted during the dry season, although they were higher during the wet season (Table and Figure ). Given the observed magnitude of nongrowing season CH 4 fluxes, our results support the emerging view that nearly continuous observations may be required to accurately estimate annual CH 4 budgets from temporarily flooded subtropical wetlands (Treat et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…We also calculated cumulative fluxes of each scalar during the dry and wet seasons to investigate whether the dominance of climatic and plant‐mediated factors controlling CH 4 fluxes from wetlands vary between the growing and the nongrowing seasons. A recent study showed that in high‐latitude wetlands, modeled CH 4 emissions during the nongrowing season tend to be smaller than observations, suggesting that factors driving CH 4 emissions and likely other GHGs could differ between seasons (Treat et al, ). In this study, measurements were done from 1 July 2013 to 31 December 2015.…”
Section: Methodsmentioning
confidence: 99%
“…While high‐latitude interannual flux measurements remain rare, in recent years towers have made considerable efforts to run continuously, bolstering our knowledge base on dormant season measurements (Figure c). It is increasingly clear that CH 4 fluxes in the dormant season comprise a large percentage of total ecosystem fluxes (Morin, Bohrer, Naor‐Azrieli, et al, ; Taylor et al, ; Zona et al, ) and that nongrowing season fluxes must be included when estimating regional CH 4 fluxes (Treat et al, ). One study in the arctic determined that dormant season fluxes were the dominant source to the annual budget (Zona et al, ).…”
Section: Temporal Distributionmentioning
confidence: 99%